Exchange Rate, Exchange Rate Volatility and Stock Prices: An Analysis of the Symmetric and Asymmetric Effect Using ARDL and NARDL Models - La Ode Saidi; Abd Azis Muthalib; Pasrun Adam; Wali Aya Rumbia; La Ode Arsad Sani (Australasian Accounting, Business and Finance Journal, 2021)
This article examined the symmetric and asymmetric effects of the IDR/USD exchange rate and its volatility on stock prices using the monthly time series data of the IDR/USD exchange rate and the Indonesian composite stock price index from January 2006 to July 2019. The data were analyzed using ARDL and NARDL models. The results showed that in the short term, the IDR/USD exchange rate has a symmetry effect on stock prices, while volatility lacks such a symmetric influence. However, these two variables asymmetrically affect stock prices, Furthermore, in the long term both the exchange rate and the volatility lack symmetric and asymmetric influence on stock prices.
Keywords: Exchange rate; exchange rate volatility; stock prices; ARDL model; NARDL model